Comparative Analysis Of Aqua MODIS and VIIRS Sensors In Mapping Chlorophyll-A Concentration and Sea Surface Temperature In The South Coast Of East Java - Fitrah Alfi Syah Alam; Hendrata Wibisana (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The South Coast of East Java is one of the areas that has marine and fisheries potential. This is utilized by local residents as a source of livelihood. To maximize this potential, it is necessary to know how the water quality in an area. The water quality of a water body can be known through the measurement of chlorophyll-a concentration and sea surface temperature with the help of remote sensing technology. This study aims to analyze the comparison of Aqua MODIS and VIIRS images on mapping chlorophyll-a concentration and sea surface temperature with the help of the SeaDAS application whose data is downloaded through the NASA oceancolor website. To map chlorophyll-a concentration and sea surface temperature, an analysis method using the most optimal mathematical model is needed. The results of the Aqua MODIS satellite image chlorophyll-a concentration research in the year (2020-2024) in the South Coast of East Java has an average of 0.24282 mg/m3, 0.19144 mg/m3, 0.51777 mg/m3, 0.37524 mg/m3, and 4.0542 mg/m3. The highest average chlorophyll-a concentration value of Aqua MODIS satellite imagery occurred in May 2024. This condition indicates that the water quality in the South Coast of East Java is low. While the chlorophyll-a concentration of VIIRS satellite images in the year (2020-2024) in the South Coast of East Java has an average of 0.23197 mg/m3, 0.31974 mg/m3, 0.19304 mg/m3, 0.38974 mg/m3, and 1.58583 mg/m3. The highest average chlorophyll-a concentration value of VIIRS satellite imagery occurred in May 2024. This condition indicates that the water quality in the South Coast of East Java is low.